Penile Revascularization for Erectile Dysfunction: a Systematic Review and Meta-Analysis of Effectiveness and Complications - Babaei, Ali Reza; Safarinejad, Mohammad Reza; Kolahi, Ali Asghar (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:FA; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: Patients with arteriogenic erectile dysfunction (ED) caused by traumatic localized arterial lesions can be treated successfully by penile revascularization (PR) surgery. We aimed to determine the subjective and objective outcomes of PR surgery in patients with arteriogenic ED. Materials and Methods: We searched for relevant publications released up to May 2008 in the Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, and Biological Abstracts. The citation lists of review articles and included trials were also searched. Published studies on different operative techniques of PR for men with ED due to traumatic penile arterial lesions were selected by 2 reviewers. Data on participantsâ€™ characteristics, study quality, population, intervention, cure and adverse effects were collected and analyzed. Results: There were 25 studies that compared the selected operative techniques. Concerning subjective cure, the results in men younger than 30 years old were better than older ones (odds ratio, 3.7; 95% confidence interval, 2.2 to 6.4; P = .001). Venous leak (odds ratio, 1.8; 95% confidence interval, 1.2 to 2.6) and history of smoking (odds ratio, 3.4; 95% confidence interval, 2.2 to 5.6) influenced success rate. Inconsistent measurements of outcomes limited the findings, and none of the studies were randomized controlled trials. Conclusion: Traumatic patients with arteriogenic ED might benefit from PR. Patient selection is vital for a successful outcome. Variations in penile vascular anatomy are also likely to be important when individualizing penile revascularization procedures. In a limited number of highly selected individuals PR can be successful for the long-term. Randomized controlled trials examining different PR techniques are needed to better examine the PR techniques.